2015
DOI: 10.1016/j.cossms.2014.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Advanced techniques for characterization of ion beam modified materials

Abstract: Keywords:Rutherford backscattering spectrometry Raman spectroscopy X-ray diffraction Small-angle X-ray scattering Positron annihilation spectroscopy Ion beam modification a b s t r a c t Understanding the mechanisms of damage formation in materials irradiated with energetic ions is essential for the field of ion-beam materials modification and engineering. Utilizing incident ions, electrons, photons, and positrons, various analysis techniques, including Rutherford backscattering spectrometry (RBS), electron RB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 50 publications
(23 citation statements)
references
References 76 publications
0
23
0
Order By: Relevance
“…To fit the intensity distribution and gain structural parameters, a hard‐cylinder model (before UV illumination) and a core–shell cylinder model (after UV illumination) were used. Details on the SAXS measurements and models can be found in previous studies …”
Section: Methodsmentioning
confidence: 99%
“…To fit the intensity distribution and gain structural parameters, a hard‐cylinder model (before UV illumination) and a core–shell cylinder model (after UV illumination) were used. Details on the SAXS measurements and models can be found in previous studies …”
Section: Methodsmentioning
confidence: 99%
“…There also exist a variety of particle beam methods which use ion beams for the acquisition of defect profiles. Although most of them are destructive techniques, there also exist some nondestructive methods such as Rutherford backscattering spectrometry [38] or positron annihilation spectroscopy (PAS). The latter is sensitive to vacancy-like defect concentrations in the range from 10 15 to 10 19 cm −3 [39].…”
Section: A Comparison To Other Techniquesmentioning
confidence: 99%
“…Electronic effects are of significant importance in a wide variety of fields where high energy irradiation processes take place, including nuclear applications, the semiconductor industry, material synthesis, modification and characterization [1,2]. The importance of the coupling of electronic and atomic processes in ionic and covalent materials has been emphasized in recent studies [3][4][5][6][7][8][9][10][11][12][13][14][15]1], where it has been shown that these effects can have linearly additive [3][4][5][6][7][8] or competing [9][10][11] impacts on the defect production.…”
mentioning
confidence: 97%
“…We find temperature dependence of the ion track size. We also find a threshold in the electronic energy loss for a given pre-existing defect concentration, which indicates a threshold in the synergy between the inelastic and elastic energy loss.Ó 2015 Acta Materialia Inc. All rights reserved.Electronic effects are of significant importance in a wide variety of fields where high energy irradiation processes take place, including nuclear applications, the semiconductor industry, material synthesis, modification and characterization [1,2]. The importance of the coupling of electronic and atomic processes in ionic and covalent materials has been emphasized in recent studies [3-15,1], where it has been shown that these effects can have linearly additive [3][4][5][6][7][8] or competing [9-11] impacts on the defect production.…”
mentioning
confidence: 99%